Body image dan tingkat kebahagiaan pada wanita dewasa awal - Firma Aulia Maulani (Fakultas Psikologi, 2019)
Body image is a form of self-assessment which appears based on societies’ perspective. Someone will categorized their self whether they are included or not to the standard of beauty. This condition leads to the satisfaction of their body. However, some experts argue that happiness is a synonym of life satisfaction. It can be concluded that someone will happy when they have been satisfaction to their life. Women in early adulthood have a tendency to focus on their appearance (self-focused). Therefore, they are more focus to take care of their self rather than being involved in social obligation. This current study was conducted to investigate whether body image had an influence or not to the happiness level especially on the women in early adulthood. The total subjects were 150 people. They applied body image scale which is developed by the researcher used body image aspects from cash and happiness scale based on the Subjective Happiness Scale and Satisfaction of Life. The result of this current study showed that there was an influence with r square score = 0,234. In conclusion, variable X (body image) was influence to variable Y (happiness) with 23, 4% of influence score.